Justice Deprived, Justice Demanded: Afropentecostalisms and the Task of World Pentecostal Theology Today - Amos Yong (Journal of Pentecostal Theology 2006; 15; 127, 2006)
By and large, Pentecostal theology has proceeded with little attention to black pentecostalism except as `objects' of historical or sociological analysis. But what does Afropentecostalism-black Pentecostalism in its global contexts-have to contribute to the formulation of a world Pentecostal theology for the twenty-first century? The works of Frank Chikane in South Africa, Robert Beckford in Britain, and Cheryl Sanders in North America are discussed and analyzed as points of entry into the theology of afropentecostal churches. This essay assumes that the future of world Pentecostal theology cannot ignore the important contributions of Afropentecostal theological traditions.